Hasil Belajar Melalui Metode Kooperatif Tipe Team Games Tournament Pada Materi Bkhulafa Urrasyidin Mata Pelajaran Ski Kelas X Di MA Yasni Sukaraja - Supenti, Yosi; Ismail, Deden Muhammad; Pratama, Rio; Lubis, Wildan Khoir; Mubarok, Dasep Hanan (Universitas Pakuan, 2025)
LEARNING OUTCOMES THROUGH A COOPERATIVE METHOD OF TEAM GAMES TOURNAMENT (TGT) TYPE IN BKHULAFA URRASYIDIN MATERIAL FOR CLASS X SKIING SUBJECTS AT MA YASNI SUKARAJAThis study aims to determine the learning outcomes through the cooperative learning model of the Teams Games Tournament type on the material of Khulafa Urrasyiddin in the SKI subject of Class X at Ma YASNI Sukaraja. The model in this study uses the Classroom Action Research (CAR) model which is carried out in two cycles. Each cycle consists of the planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests, observation, and documentation. The results of the study showed an increase in students' cognitive learning outcomes after the Teams Games Tournament method was applied. In cycle I, the average student score was 62.50, with 30% of students achieving the Minimum Completion Criteria (KKM). In Cycle II, the average score was 69.42 and 80% of students achieved KKM. Thus, the application of Teams Games Tournament has proven effective in improving students' cognitive learning outcomes on the material of Khulafa Urrasyiddin. This strategy helps students understand concepts visually and systematically, so that they can improve their understanding in the learning process.